Mouse Protein Z-Dependent Protease Inhibitor cDNA - Zhang, Jing; Broze, George J., Jr. (Thrombosis and Haemostasis, 2001)
Protein Z-dependent protease inhibitor (ZPI) is plasma proteinase inhibitor in the serpin superfamily that produces rapid inhibition of factor Xa in the presence of phospholipids, Ca++ and protein Z (PZ). Mouse ZPI cDNA was isolated and cloned from mouse liver RNA using RT-PCR. The cDNA contains 100 nucleotides 5’ of a translation initiation codon and an open reading frame of 1344 nucleotides followed by a 163 nucleotide 3’ untranslated sequence with a poly (A) tail. The cDNA predicts a signal peptide containing 21 amino acids and a mature protein of 427 residues with 8 potential sites for N-linked glycosylation. The oligonucleotide and predicted amino acid sequences of mouse ZPI are 72% and 81% homologous with those of human ZPI. Like human ZPI, mouse ZPI contains tyrosine-serine (P1-P1’) at its reactive center in contrast to the rat molecule which contains tyrosinecysteine. By Northern analysis, mouse ZPI mRNA is 1.6 kb in size and, similar to both human and rat, it is detectable in liver, but not in heart, brain, spleen, lung, kidney, skeletal muscle or testes.
Keywords: Proteinase inhibitor; serpin; mouse